COVID-19 OUTBREAK IN EUROPE AND ITS IMPACT ACROSS FOUR DIFFERENT SECTORS: ANALYTICAL RESEARCH - GIAMMANCO, Maria Daniela; GITTO, Lara (Journal of European Economy, 2021)
The ambition of this contribution is to outline how the European perspective – that of economists and social science scholars who have observed and studied Covid-19 in the last 16 months, has been represented in the more popular journals worldwide dealing with Agriculture, Education, Health and Tourism. The first two sectors, Health and Education, have been chosen because of the relevance of the merit goods provided, not only for the present wealth, but for the future development of society. Tourism has been selected because this sector has been savagely devastated by the pandemic due to the necessary restrictive governmental measures imposed to avoid the virus spreading. Agricultural sector plays an important role in the European economy especially for the countries with the lowest income. The trend found among the considered journals, which were selected out of those with the highest h-index through the search engine Scimago, was to publish a few selected contributions or, oftentimes, to dedicate a special issue of the journal to the economic consequences of the pandemic. Since this survey is aimed at summarizing the European evidence, some of the identified studies were not considered, most of them concerning the Asian Far East countries (the geographic area from where the contagion began) and the USA (the country with the highest number of deaths due to Covid-19). JEL: C83, H12, I18, I21, O13, Z32.